Seduction, Sharing Stories, and Borderlinking in Co-Constructed Narratives - Voela, Angie; Esin, Cigdem; Achan, Jennifer (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2020)
Drawing on a co-constructed autobiographical narrative as our example, we explore the resonances of Catherine Kohler Reissman’s concept of seduction with Bracha Lichtenberg Ettinger’s concept of matrixial borderlinking. Borderlinking between theoretical domains, rather than comparisons or juxtaposition, brings forth potentialities and expands the theorization of feminine subjectivities in much the same way as co-constructed narratives celebrate the we without obliterating the I.